Production of Aesthetic Tastes and Creativity Education of Indonesian Glass Painting Artists - Casta, Casta; Rohendi Rohidi, Tjetjep; Triyanto, Triyanto; Karim, Abdul (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study aims to find the repertoire of aesthetic taste as a creative act and its relation to symbolic power in the arena of Indonesian cultural production of glass painting. The study used a qualitative approach with a phenomenological design. Data collection used in-depth interviews, participant observation, individual life’s history, and document examination. Data analysis used interpretive phenomenological analysis. The study finds five aesthetic taste repertoires that include: (1) the aesthetic taste of the palace which is characterized by the symbolic decorative visualization of calligraphy pictographs of petarekatan with wadasan and mega mendung ornaments; (2) the taste of strengthening cultural identity is marked by the symbolic decorative visualization of a traditional sourcebook for puppet shadow objects with wadasan and mega mendung ornaments; (3) the taste of traditional renewal is characterized by liberating expressive decorative visualizations; (4) the taste of cultural revitalization is characterized by decorative visualization of the superiority of tradition which is involute; and (5) the taste of marginalized community is characterized by the simplicity of traditional object visualizations. The five aesthetic tastes carry a decorative expression style with an interpretation of tradition based on the cultural capital of the artists. The production of aesthetic taste cannot fully be used to classify the social class structure of appreciators but is related to the identity of the cultural capital they have. The production of aesthetic taste is a creative education model that responds to the doxa of symbolic power in the form of orthodox or heterodox, resulting in defensive, subversive, defensive-subversive synthesis, and pseudo-subversive strategies, which are fought for legitimacy as symbolic power.